Influence of lysine concentration on growth performance and carcass characteristics of finishing pigs - Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used a total of 11,653 pigs to examine the influence of a lysine phase-feeding regimen on growth performance and carcass characteristics in finishing pigs. We found that the lysine regimen did not affect ADG. Also, the low-lysine regimen was adequate for maximizing growth performance and carcass characteristics of barrows. However, the low-lysine regimen was inadequate to optimize feed efficiency in gilts. Further analysis indicated that the largest differences in feed efficiency were for the 115 to 160 lb period in gilts. Later in the growth period, feed efficiency of gilts was similar across dietary lysine regimens.
Keywords: Swine; Lysine requirement; Finishing pigs